2006
DOI: 10.1093/rpd/ncl022
|View full text |Cite
|
Sign up to set email alerts
|

Natural radionuclides and dose estimation in natural water resources from Elba protective area, Egypt

Abstract: The concentrations of the natural radionuclides (226)Ra, (232)Th and (40)K in 15 different water samples from Elba protective area, south-eastern desert of Egypt, have been determined using NaI(Tl) detector. Gamma ray spectrometric analysis was performed and the concentrations obtained for each of the radionuclides expressed in Bq l(-1) ranging from 1.6 to 11.1 for (226)Ra, 0.21 to 0.97 for (232)Th and 9.1 to 23 for (40)K. A reasonable correlation was found between (226)Ra, (232)Th concentrations and pH, altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 13 publications
3
16
1
Order By: Relevance
“…Also Th activity concentrations obtained in this study match with that reported by Saqan [25] for hot spring water at Afra, Barbeita and Al-Amir sites in Jordan and is higher than that reported by [20,21,23,24], and lower than that reported by Agbalagba [26] for lake water in Nigeria. On the other hand, 40 K values in the present study match with those values reported by El-Mageed et al [3] for spring water Yemen (Dempt) and El Arabi [24] for groundwater in Egypt (Elba) and lower than values reported by Agbalagba [26] in Nigeria.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Also Th activity concentrations obtained in this study match with that reported by Saqan [25] for hot spring water at Afra, Barbeita and Al-Amir sites in Jordan and is higher than that reported by [20,21,23,24], and lower than that reported by Agbalagba [26] for lake water in Nigeria. On the other hand, 40 K values in the present study match with those values reported by El-Mageed et al [3] for spring water Yemen (Dempt) and El Arabi [24] for groundwater in Egypt (Elba) and lower than values reported by Agbalagba [26] in Nigeria.…”
Section: Resultssupporting
confidence: 86%
“…As can be seen from Table 3, 226 Ra values from the present work are higher than that reported by Ahmed [20] for ground water in Egypt (Qena and Safaga), Al Fatih [21] for ground water in Sudan, Zhuo [22] for ground water in China, Kpegl [23] for surface water in Ghana. Also it's found that they are lower than the values reported by [24], [25], [26] and [4]. Also Th activity concentrations obtained in this study match with that reported by Saqan [25] for hot spring water at Afra, Barbeita and Al-Amir sites in Jordan and is higher than that reported by [20,21,23,24], and lower than that reported by Agbalagba [26] for lake water in Nigeria.…”
Section: Resultssupporting
confidence: 81%
“…This value was only 1.5 times higher than the value reported by El Arabi et al (2006) in natural water resources from Elba protective area in Egypt [13]. …”
Section: Resultscontrasting
confidence: 53%
“…Similarly, Zhuo et al (2001) [7] reported the maximum value of 0.93 Bq L -1 was found in groundwater sample taken in Fujian province (Table 2). Nevertheless, some samples contained higher concentrations of 226 Ra were observed in groundwater samples taken in Egypt [8] and Yemen [9] and Serbia [10]. However, there is a report of 226 Ra monitoring in groundwater samples taken in Roi-Et Province, northeastern part of Thailand [14].…”
Section: ) Radium-226mentioning
confidence: 99%